Bakul Rahmah KPT-UMP helps flood victims in Kota Tinggi - Mimi Rabita, Abdul Wahit (2023)
KOTA TINGGI, 30 January 2023 - Universiti Malaysia Pahang (UMP) mobilised the Southern Flood Volunteer Mission by distributing donations to help flood victims in Teluk Hutan Lesung Village, Tanjung Sedili, Kota Tinggi.